INNOVATIVE APPROACHES IN DEVELOPING EXPORT ACTIVITIES IN UZBEKISTAN (MULTIDISCIPLINARY JOURNAL: FUNDAMENTAL RESEARCH SCIENTIFIC JOURNAL, 2025)
This article analyzes the role and importance of innovative approaches in the development of export activities in Uzbekistan. The article discusses the impact of exports on economic growth, export diversification, capturing new markets, and strategies for developing exports through digital technologies and innovative systems. It also highlights how effective approaches and the application of modern technologies in exporting domestically produced goods create new opportunities, and the importance of state policy in promoting exports. Additionally, the article analyzes the challenges in export development and the ways to overcome them.